Feeding and growth efficiency of Pacific white shrimp (Litopenaeus vannamei) fed with acid fish silage as dietary protein source - Visto, Raycen V. (2018.)
A 60-day feeding trial was performed to evaluate the effects of acid fish silage (FS) as dietary protein replacement for fish meal on the growth performance of the Pacific white shrimp (Litopenaeus vannamei). Four hundred fifty (450) post larvae of white shrimps (average body weight = 0.01g) were randomly distributed into 15 experimental tanks. Five experimental diets were formulated and fed to groups of shrimps : 0% fish silage (FS), 12.5% FS, 25% FS, 37.5% FS and 50% FS replacing fish meal. After the feeding trial, each group of shrimps were subjected to Vibrio parahaemolyticus challenge. Attractability test was also performed on a different batch of white shrimps. At the termination of the trial, weight gain (WG) and specific growth rate (SGR) of the FS-supplemented groups were higher than that of the control group ; however,25% FS group did not differ from that of the 37.5% FS. Feed conversion ratio (FCR), protein efficiency ratio (PER) and survival rate did not differ significantly among experimental groups. Replacing 50% of dietary protein by FS resulted in a 43% improvement in growth. Bacteria challenge trial showed that there was significant protective effect of feeding FS over those fed the control diet, improving the survival rate of infected shrimps by 371%. A minimum replacement level of 24.5% the protein source by FS was estimated using the data on mortality rates of the Vibrio challenge tests. Results of the attractability test showed no significant differences except between the control and 50 FS groups. The findings revealed that FS could serve as an alternative protein source to replace fishmeal up to 50% due to its high EAAI of 0.84. FS serves as a very good feeding stimulant at 50% inclusion. FS served as an immunostimulant against V. parahaemolyticus in L. vannamei.
Thesis (M. S. Fisheries-Aquaculture) -- [Miagao, Iloilo] : University of the Philippines Visayas, June 2018.